Labour Elasticity in V4 countries: Structural decomposition analysis - Martin Hudcovský; Martin Lábaj; Karol Morvay (University of Economics in Bratislava, Department of Economic Policy, 2015)
In the present paper, we analyse determinants of labour elasticity in V4 countries. While the standard approach relies on the parametric estimation of labour elasticity coefficients, we employ a novel approach based on structural decomposition analysis. This allows us to identify several determinants that mitigate the effects of economic growth on employment. We decompose the overall change in employment into the contribution of six factors: changes in labour productivity, changes in import of intermediate products, changes in the structure of production, changes in the final demand structure by industries and by sectors, and a change in final demand volume. We show that besides generally accepted influence of labour productivity growth on employment other factors such as structural changes and changes in final demand played an important role in employment changes. These results shed some light on low labour elasticity in V4 countries that goes beyond the simple labour productivity growth argument.
Keywords: C67; J21; 330; structural decomposition analysis; labour elasticity; V4 countries; input-output analysis